Dynamics of a model for the degradation mechanism of aggregated α-synuclein in Parkinson's disease - Yang, Bojie; Yang, Zhuoqin; Hao, Lijie (Frontiers in Computational Neuroscience, 2023)
Accumulation of the misfolded synaptic protein α-synuclein (αSyn*) is a hallmark of neurodegenerative disease for Parkinson's disease (PD). Recent studies suggest that autophagy lysosome pathway (ALP) including both Beclin1-associated and mTOR-signaling pathways are involved in αSyn* clearance mechanism. In this work, we propose a mathematical model for αSyn* degraded by ALP with the crosstalk element of mTOR. By means of codimension-1 bifurcation analysis, we survey tri-stability for αSyn* under three different stress signals, i.e., the low, intermediate and high steady states parallel to the healthy, critical and disease states of pathology of PD, respectively. We further consider the regulations of the Beclin1- and mTOR-dependent rate on the αSyn* degradation by condimension-1 and -2 bifurcation diagrams. We find that especially under the internal and external oxidative stresses (S_1), the bistable switch of the aggregation of αSyn* can be transformed from irreversibility to reversibility through the ALP degradation pathways. Furthermore, we probe robustness of tri-stability for the stress S_1 to the parameters related to mTOR-mediated ALP. That confirms that mTOR-mediated ALP is important for maintaining the essential dynamic feature of tri-stability. Our work may provide a promising application to further experiments and simulations of the degradation mechanism of PD dynamic modelling.